Tracking the evolution of particulate organic matter sources during summer storm events via end-member mixing analysis based on spectroscopic proxies. (August 2020) - Derrien, Morgane; Lee, Mi-Hee; Choi, Kwangsoon; Lee, Kwang-Sik; Hur, Jin
Abstract: Despite the growing attention to the effects of hydrological precipitation on organic carbon export along the continuum land-river-ocean, limited effort has been made to understand the export and the reactivity of particulate organic carbon (POC) compared to those of dissolved organic carbon (DOC). Yet, further understanding of the controlling mechanisms on the export of particulate organic matter (POM) from terrestrial systems is fundamental. In this study, we assessed the temporal changes of the source contributions to riverine POM in two adjacent rivers of the same watershed during two summer storm events, which included the early and the late events, using end-member mixing analysis (EMMA) based on spectroscopic proxies. The EMMA showed relatively high contributions of terrestrial materials to the riverine POM for both rivers during the early summer storm event. However, this trend did not persist until the late summer storm event, which presented the decreased contributions of the terrestrial sources and less dynamic changes in the source distributions compared to those observed in the early summer rain event. These results demonstrate the combined impacts of the land use/surrounding area, the hydrology, and the intra-seasonal variations on the dominant riverine POM sources. This study provides an interesting insight into the importance of the intense hydrological events on the export of the terrestrial OM and further on the potential modification of the existing carbon mass balance along the continuum land-river-ocean. Graphical abstract: Image 1 Highlights: POM storm samples were characterized using fluorescence spectroscopy. EMMA based on fluorescence proxies was applied for POM source tracking. Variations on POM sources are affected by land use, hydrology, and season. Differences in the dominant POM sources are found between early and late rainfalls. It shows the effects of intense hydrological events on terrestrial POM export.